The Impact of a Local Well-Being Philosophy on Revisit Intentions to Bali Among Digital Nomads - Hanugerah Kristiono Liestiandre; Alastair M. Morrison; Ni Nyoman Kerti Yasa; Tjok Gd Raka Sukawati; I. Putu Gde Sukaatmadja (Tourism and Hospitality)
The level of success in tourism is gauged by several metrics; however, the most widely used is the level of tourist arrivals. However, this research answered the call for greater investigation of the impacts of qualitative factors and intangible cultural–heritage assets on destination performance. The primary research purpose was to analyze the effect of implementing a local well-being philosophy (Tri Hita Karana) on tourist revisit intentions for Bali and the mediation of destination quality and destination image. A research model was developed to examine the relationships among local wisdom (TKH), destination quality, destination image, and revisit intentions. Data were collected via a survey of 520 digital nomadic tourists and analyzed using SmartPLS 4. The results indicated that the implementation of THK positively and significantly affected revisit intentions, destination image, and destination quality. Destination image and destination quality had positive and significant effects on revisit intentions, and destination image and destination quality also significantly mediated the effect of THK implementation on revisit intentions. The findings suggested that implementing local wisdom values such as THK in the management of a destination makes visitors feel more favorably about the quality and image of the destination and they have the intention to revisit.